2023
DOI: 10.1021/jacs.2c12850
|View full text |Cite
|
Sign up to set email alerts
|

Azolation of Benzylic C–H Bonds via Photoredox-Catalyzed Carbocation Generation

Abstract: A visible-light photoredox-catalyzed method is reported that enables the coupling between benzylic C−H substrates and N−H azoles. Classically, medicinally relevant N-benzyl azoles are produced via harsh substitution conditions between the azole and a benzyl electrophile in the presence of strong bases at high temperatures. Use of C−H bonds as the alkylating partner streamlines the preparation of these important motifs. In this work, we report the use of N-alkoxypyridinium salts as a critically enabling reagent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…In the case of unsymmetric pyrazoles, 65–90% yield, 92:8–99:1 er , and nitrogen regioselectivity (N 2 :N 1 > 20:1) were observed ( 3j – 3o ). X-ray crystallographic analysis of 3j confirmed the coupling of cyclopropene with the more sterically hindered nitrogen of the pyrazole; this regioselectivity is rare in pyrazole functionalization. ,, Further NOE experiments confirmed similar regiocontrol for related pyrazole substrates (see the SI). Despite the presence of a competing amino group, 3l was isolated exclusively, showing a highly chemoselective cyclopropylation for pyrazole nitrogens.…”
mentioning
confidence: 80%
“…In the case of unsymmetric pyrazoles, 65–90% yield, 92:8–99:1 er , and nitrogen regioselectivity (N 2 :N 1 > 20:1) were observed ( 3j – 3o ). X-ray crystallographic analysis of 3j confirmed the coupling of cyclopropene with the more sterically hindered nitrogen of the pyrazole; this regioselectivity is rare in pyrazole functionalization. ,, Further NOE experiments confirmed similar regiocontrol for related pyrazole substrates (see the SI). Despite the presence of a competing amino group, 3l was isolated exclusively, showing a highly chemoselective cyclopropylation for pyrazole nitrogens.…”
mentioning
confidence: 80%
“…Despite these important advances, expansion of N -nucleophile identity beyond nitriles in solvent quantity has been comparatively less explored. Copper-catalyzed platforms, including variants of the original Karasch–Sosnocky reaction as well as more recent developments by Stahl, Liu, and others, have proven most versatile, enabling C–H (sulfonyl)­amidation, azolation, and azidation. , Alternatively, transition-metal-free platforms for C­(sp 3 )–H (sulfonyl)­amidation and C­(sp 3 )–H azolation exist, but each method and set of reaction conditions is confined to a single nucleophile class (amides, sulfonamides, or azoles, but never all three within one protocol) (Figure B). Moreover, many still require stoichiometric oxidants such as Selectfluor, NFSI, or DDQ.…”
Section: Introductionmentioning
confidence: 99%
“…Copper-catalyzed platforms, including variants of the original Karasch-Sosnocky reaction 6 as well as more recent developments by Stahl, Liu, and others have proven most versatile, enabling C-H (sulfonyl)amidation, [7][8][9][10][11][12][13] azolation, 14 and azidation. 15,16 Alternatively, transition metal-free platforms for C(sp 3 )-H (sulfonyl)amidation [17][18][19] and C(sp 3 )-H azolation [20][21][22][23] exist, but each method and reaction conditions is confined to a single nucleophile class (amides, sulfonamides, or azoles, but never all three within one protocol). Moreover, many still require stoichiometric strong oxidants such as Selectfluor, NFSI, or DDQ, which limit the scope of the methods.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Musacchio and coworkers reported only a single example of C-N bond formation using a pyrazole derivative; 25 they have since expanded this catalyst platform to include secondary benzylic and tertiary benzylic and aliphatic C(sp 3 )-H azolations. 23 In our original report, inclusion of NEt3•3HF was necessary in order to obtain high yields of C(sp 3 )-H functionalization (even for non-fluoride nucleophiles), likely because this additive accelerated single-electron reduction and decarboxylation of N-acyloxyphthalimide with excited-state Ir(p-F-ppy)3, affording higher concentrations of the HAT reagent (methyl radical). However, we found that NH-nucleophiles such as sulfonamides and amides were deactivated by competitive hydrogen bonding with the NEt3•3HF additive.…”
Section: Introductionmentioning
confidence: 99%